Transcutaneous Doppler ultrasound measurement of superior mesenteric artery blood flow in man. (January 1986) - Qamar, M I; Read, A E; Skidmore, R; Evans, J M; Wells, P N
Abstract : A duplex scanner which consists of a real time two dimensional scanner and a pulsed Doppler flowmeter was used to measure superior mesenteric blood flow in 70 healthy subjects. By processing the Doppler shift signals, the instantaneous average Doppler shift frequency and then the instantaneous average velocity of the flow rate were calculated. Both diameter of the vessel and angle between vessel and beam were measured from real time imaging. The mean (+/- standard error of the mean) of the superior mesenteric blood flow was 517 +/- 19 ml/min. There was neither significant difference in flow between sexes, nor correlation between flow and age (r = 0.042). The mean of coefficients of variability were 6.8% over the short term, and 8.2% in long term studies.